Obernewtyn - Carmody, Isobelle (New York : Random House, 2008)
Elspeth Gordie, living in orphanages in the aftermath of the holocaust known as the Great White, is desperate to get her certificate of normalcy, but her mental powers--a result of the radiation that ravished the land--persist in making themselves known despite her efforts to hide them.
Library Journal
Publisher's Weekly
Teacher Librarian
Young Adult.
Young Adult
Keywords: Extrasensory perception -- Juvenile fiction; Friendship -- Juvenile fiction; Human-animal communication -- Juvenile fiction; Orphans -- Juvenile fiction; Persecution -- Juvenile fiction; Extrasensory perception -- Fiction; Friendship -- Fiction; Human-animal communication -- Fiction; Orphans -- Fiction; Persecution -- Fiction; Science fiction; Communication -- Fiction; Extrasensory perception -- Fiction; Friendship -- Fiction; Orphans -- Fiction; Persecution -- Fiction; Science fiction